Ordinary meaning : a theory of the most fundamental principle of legal interpretation - Slocum, Brian G. (Chicago : The University of Chicago Press, 2016)
Brian Slocum builds his argument for a new method of interpretation by asking glaring, yet largely ignored, questions. What makes one particular meaning the 'ordinary' one, and how exactly do courts conceptualise the elements of ordinary meaning? He provides a revised framework, boldly instructing those involved with the law in how the components of ordinary meaning should be properly identified and developed in our modern legal system.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 25, 2016).
Keywords: Law -- Language; Communication in law; Law -- Terminology; Law -- Interpretation and construction; Law -- United States -- Terminology; Law; Jurisprudence & general issues